ACIDITY AND ALKALINITY LEVEL OF MAYAN BAMBOO ACTIVATED CHARCOAL (MBAC) ON SATURATED VAPOR OF ACID CHLORIDE AND NATRIUM HYDROXIDE - Novitri Hastuti; Gustan Pari; Dadang Setiawan; Mahpudin Mahpudin; Daud Mulia Godang (Widyariset, 2015)
The use of a strong acid  and alkali  gives some disadvantages such as large volume, needs washing process and expensive in cost. The use of activated charcoal as a solid catalyst has grown but its adsorption performance can be affected by the activation process. This study aimed to characterize Mayan bamboo activated charcoal/MBAC (Giganchlotoa robusta Kurz). Carbonization was carried out at  temperature  500°C for 4-5 hours. The charcoal was activated by steam at temperature 800°C for 60 minutes and 90 minutes.  Activated carbon from Mayan bamboo tested for  its acidity and alkalinity  by saturated vapor of HCl and NaOH in a desiccator for 5 days. Characterization of Mayan bamboo activated showed that the moisture content, ash content, volatile matter and fixed carbon  met the Indonesian standards (SNI 06-3730-1995). For adsorption capacity of iodine only MBAC in activation time, 90 minutes met Indonesian standard. The crystallinity of MBAC in activation time 90 minutes is 47.58% higher than MBAC in activation time 60 minutes about 25.65%. Adsorption of saturated vapor of HCl and NaOH showed MBAC in activation time 60 minutes is more acidic whereas MBAC in activation time 90 minutes is more alkaline. MBAC is can be used as a solid catalyst for various applications.